The parliamentarization of EU trade policy: unveiling the European Parliament’s involvement in EU-MERCOSUR trade negotiations - Pasquariello Mariano, Karina L. [UNESP]; Theodoro Luciano, Bruno (Taylor & Francis, 2018)
Over the past decades the European Parliament (EP) has achieved a prominent position in the European Union’s decision-making process. Although EP consent has been a requirement for the final approval of EU trade agreements since the Treaty of Lisbon, its role in the process of negotiating these agreements remains unclear. In order to illustrate this context with a case study, we will investigate the ongoing trade negotiations between the EU and the Southern Common Market (MERCOSUR), which have started in 1999 and were temporarily suspended between 2004 and 2010. The degree of autonomy parliamentarians have to deviate from the European Commission’s position is verified, as well as their information clearance level and the degree of political polarization associated with this agreement. Therefore, this research intends to assess how parliamentarians seek to influence trade agreements while the negotiations are still in course, thus strengthening the parliamentarization of EU trade policies.
Keywords: EU-MERCOSUR trade agreement; European Parliament; European Union; MERCOSUR; parliamentarization